Import competition and response - Bhagwati, Jagdish N. (Chicago : University of Chicago Press, 1982)
The theoretical papers offer several novel approaches to the analysis of protectionist lobbying, provide important contributions to the analysis of the adjustment costs imposed by import competition, and yield insights into the appropriate design of adjustment assistance
Papers presented at the National Bureau of Economic Research Conference on Import Competition and Adjustment: Theory and Policy held in Cambridge, Mass., May 8-11, 1980.
Includes bibliographies and indexes.
II 16/01/2019
Loans
Keywords: Trade adjustment assistance